Putting Photosystem I to Work: Truly Green Energy. Issue 12 (December 2020) - Teodor, Alexandra H.; Bruce, Barry D.
Abstract : Meeting growing energy demands sustainably is one of the greatest challenges facing the world. The sun strikes the Earth with sufficient energy in 1.5 h to meet annual world energy demands, likely making solar energy conversion part of future sustainable energy production plans. Photosynthetic organisms have been evolving solar energy utilization strategies for nearly 3.5 billion years, making reaction centers including the remarkably stable Photosystem I (PSI) especially interesting for biophotovoltaic device integration. Although these biohybrid devices have steadily improved, their output remains low compared with traditional photovoltaics. We discuss strategies and methods to improve PSI-based biophotovoltaics, focusing on PSI-surface interaction enhancement, electrolytes, and light-harvesting enhancement capabilities. Desirable features and current drawbacks to PSI-based devices are also discussed. Highlights: Studies of alternative electrode and semiconductor materials have improved PSI orientation and activity on electroactive surfaces. Stable, photoactive dense packing of PSI on electrode and semiconductor surfaces is difficult. Crosslinking, redox polymer hydrogels, 3D semiconductor architectures, and biocompatible electrolytes could improve PSI-based device stability and output. Native PSI utilizes chlorophylls a and b for its light-harvesting antenna, leaving a 'green gap' in its absorption spectrum. Dyes and nanoparticles that can use this green gap and transfer their energy to PSI can enhance the photoactivity of PSI in vitro . PSI reduction kinetics post-photoexcitation are slow and limiting, and novel redox mediators and modified proteins to improve kinetics could improve photosensitizer regeneration rates and enhance photocurrent densities in PSI-based devices.